2010
DOI: 10.1002/pola.23911
|View full text |Cite
|
Sign up to set email alerts
|

Polymerized pickering HIPEs: Effects of synthesis parameters on porous structure

Abstract: A polyHIPE is a highly porous polymer synthesized from monomers within the external phase of a high internal phase emulsion (HIPE). The large amount of difficult to remove surfactant needed for HIPE stabilization can affect the properties of the resulting polymer. A Pickering emulsion is a surfactant‐free emulsion stabilized by solid particles that preferentially migrate to the interface. In this article, the synthesis of crosslinked polyacrylate polyHIPEs based on Pickering HIPEs stabilized using silane‐modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
134
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(142 citation statements)
references
References 53 publications
6
134
0
2
Order By: Relevance
“…Besides the viscosity, [28] the increase in mixing speed influences an increase in shear stress, which causes the formation of smaller droplets of internal phase and also reduces the thickness of the interfacial film, causing more interconnected morphology after polymerisation. [23,29,30] This can be nicely seen from the BET measurements listed in Table 2, where the surface area is increasing with increased stirring rate. Similar results have already been observed previously for MMA polyHIPE material.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Besides the viscosity, [28] the increase in mixing speed influences an increase in shear stress, which causes the formation of smaller droplets of internal phase and also reduces the thickness of the interfacial film, causing more interconnected morphology after polymerisation. [23,29,30] This can be nicely seen from the BET measurements listed in Table 2, where the surface area is increasing with increased stirring rate. Similar results have already been observed previously for MMA polyHIPE material.…”
Section: Resultsmentioning
confidence: 54%
“…[22][23][24][25] Initiators can be put in either organic or water phase or also in both phases [22,26] and can be induced by thermal decomposition, redox reactions, photolysis, etc. In the case of water-in-oil emulsions (O/W), where monomers and initiator are both soluble in organic phase, the initiation takes place inside the continuous phase, and when initiator is soluble in water phase, the polymerisation starts at the interface of both phases.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have shown that variables such as emulsion composition (Arditty et al, 2003;Binks and Whitby, 2004;Sturzenegger et al, 2012), mixing speed (Gurevitch and Silverstein, 2010;Sturzenegger et al, 2012), and particle size (Binks and Lumsdon, 2001) have impacts on the Pickering emulsion properties such as porosity and microstructure. When magnesium oxide is used to stabilize the emulsion, processing variables additionally influence the amount of brucite that is created during the sample preparation.…”
Section: Effects Of Brucite Conversionmentioning
confidence: 99%
“…Pickering emulsion properties such as drop size and porosity are adaptable by varying processing conditions. For example, mixing speed (Gurevitch and Silverstein, 2010;Sturzenegger et al, 2012), particle concentration (Arditty et al, 2003;Binks and Whitby, 2004;Sturzenegger et al, 2012), particle wettability (Akartuna et al, 2008b;Bachinger and Kickelbick, 2010;Chuanuwatanakul et al, 2011;Haase et al, 2011), particle aspect ratio (Vandebril et al, 2010), particle roughness (San-Miguel and Behrens, 2012), and particle size (Binks and Lumsdon, 2001) have all been studied. Such wet emulsions can be shaped, extruded into forms or coated into sheets because of their measurable yield stress Chen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Silverstein group published studies describing the effect of the locus of initiation on pore architecture and properties. [33][34][35][36] The authors proposed that organic-phase initiation resulted in larger, spherical, interconnected pores and an increased loss modulus relative to aqueous-phase initiation. 34 However, a mechanistic description of the effect of locus of initiation on the resulting macromer densification forces and the corollary effect on interconnect formation was not described.…”
Section: Introductionmentioning
confidence: 99%